Nutritive value of camaro. - Barrion-Dupo, A.L.A.; Barrion, A. S. A.; Lit, I. L., Jr. (2003)
Mole crickets (Gryllotalpa sp.) or aro-aro in Tagalog are known insect pests of rice in Central Luzon which local residents have resourcefully turned into seasonal spicy called Camaro. In order to assess the potential of this native delicacy as an alternative energy and protein source for Filipinos, the mean nutritive values. of the Camaro were determined through proximate analysis. Energy content of this food item was estimated based on the known percentage of protein fat and carbohydrates. The carbohydrate content was calculated as the difference between 100 and the sum of percentage of protein, moisture, fat and ash. Conversion factors used were 16.74 kilojoules (4.0 kilocalories/gram) for protein and carbohydrates and 37.66 kilojoules (9.0 kilocalories/gram) for fat. Results of the analysis showed that this stir-fried cricket dish is good source of both energy and protein. Based on the 2002 recommended energy and nutrient intake of Filipinos, a single serving of Camaro or 150 grams of this dish will meet 28% and 74% of the daily energy and protein requirements of adult Filipinos between the ages 19-49. Comparing the energy and protein content of Camaro with another common. protein source like a 150 grams fried leg showed that Camaro had higher energy and protein content. Fried chicken leg weighing 150 grams will provide around 20% and 63% of the recommended daily requirement of 19-49 year old Filipinos for energy and protein, respectively. Camaro therefore, can serve as a cheap alternative energy and protein source for Filipinos.
Keywords: Mole crickets; Cooking (Insects); Edible insects